Обработка AL 2O 3 в постоянном электромагнитном поле с заданной симметрией С 3; Известия вузов. Физика; Т. 57, № 7-2 - Клишин А. П. Андрей Петрович; Руднев С. В. Станислав Васильевич; Закутаев А. Н. Александр Николаевич; Верещагин В. И. Владимир Иванович (2014, 2014)
Заглавие с экрана